Use of Vietnam Steel Slag as Aggregate for Roller-Compacted Concrete Pavement - Lam Ngoc Tra My (Prince of Songkla University, 2021)
Thesis (Ph.D., Civil Engineering)--Prince of Songkla University, 2018